Escherichia coli individual antimicrobial resistance prevalences - Benedict, Katharine M.; Gow, Sheryl P.; McAllister, Tim A.; Booker, Calvin W.; Hannon, Sherry J.; Checkley, Sylvia L.; Noyes, Noelle R.; Morley, Paul S. (Colorado State University. Libraries, 2007)
Escherichia coli was isolated from the feces of beef cattle from four commercial feedlots in Alberta, Canada. Each individual was sampled twice, once upon arrival to the feedlot, and again at ≥33 days on feed (DOF). A total of 2,725 isolates were collected from 923 individuals. Antibiotic susceptibility of these isolates to 19 different antimicrobial drugs was determined by broth microdilution and/or disk diffusion assay. Prevalence of resistance to each drug, by sampling time, was calculated (see Figure 2 in associated publication). Data used for determination of prevalences are reported in this database.
Primary contact: Paul S. Morley (Paul.Morley@colostate.edu).
Cattle Enrolled in Study: September 2007-January 2010.
Department of Clinical Sciences
Keywords: antimicrobial resistance; antimicrobial drug; cattle; feedlot; Escherichia coli